Cobalt‐Catalyzed 2‐(1‐Methylhydrazinyl)pyridine‐Assisted Direct C−H/N−H Functionalization of Benzoyl Hydrazide with Isocyanide: Efficient Synthesis of Iminoisoindolinone Derivatives. Issue 7 (20th February 2019) - Zhao, Hua; Shao, Xiaoru; Qing, Zhineng; Wang, Taimin; Chen, Xiaoming; Yang, Hongjian; Zhai, Hongbin
Abstract: A cobalt‐catalyzed direct C−H/N−H functionalization of benzoyl hydrazide with isocyanide by utilizing 2‐(1‐methylhydrazinyl)pyridine (MHP) as a bidentate directing group has been developed. This formal [4+1] cycloaddition protocol showed high efficiency and remarkable functional group tolerance, and the ubiquitous 3‐iminoisoindolinones were obtained in good to excellent yields in the presence of the earth‐abundant cobalt catalyst. Moreover, this transformation was accomplished by employing environmentally friendly oxygen as the sole oxidant in the absence of any other additives. Abstract :